2021
DOI: 10.32535/ijabim.v6i3.1329
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hedonistic Motives, Fashion Interest, and Positive Emotions on the Impulsive Buying of Fashion Products with Sales Promotion as Moderating Variables

Abstract: This study analyzes the effect of hedonic motives, fashion involvement, and positive emotions on impulsive buying of fashion products with sales promotion as a moderating variable. This quantitative study used the accidental sampling method. The sample was 122 respondents. Analysis techniques were used based on Partial Least Square (PLS) to test the hypotheses. The results indicate that 1) hedonic motives, fashion involvement, and positive emotions have a positive and significant effect on impulsive buying fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…This result in line with the study that previously done by (Tirtayasa et al, 2020) who said that hedonism motivation influenence the online impulsive buying behavior. Similar results were also shown in research conducted by (Sitindaon & Hussein, 2022), (Utami et al, 2021) (Helmi et al, 2023). These study showed that hedonism also has significant effect to influence online impulsive buying behavior.…”
Section: Discussionsupporting
confidence: 89%
“…This result in line with the study that previously done by (Tirtayasa et al, 2020) who said that hedonism motivation influenence the online impulsive buying behavior. Similar results were also shown in research conducted by (Sitindaon & Hussein, 2022), (Utami et al, 2021) (Helmi et al, 2023). These study showed that hedonism also has significant effect to influence online impulsive buying behavior.…”
Section: Discussionsupporting
confidence: 89%
“…This glad urge emerges from within a person since shopping may truly relieve Asia-Pacific Management and Business Application, 11, 3 (2023): 347-362 exhaustion from various daily chores, even if done online, because shopping has become a pleasure in a person, even if simply glancing around is enough to make some people happy (Hursepuny & Oktafani, 2018). Finally, simply glancing around piques someone's attention when they find a selection of new things that they don't have and enticing promotional offers (Tarka et al, 2022). The findings of Ahmed et al (2020) study show that hedonic shopping motivation has a positive and significant effect on consumer impulse buying, as do the findings of Hursepuny and Oktafani's (2018) study, which also shows that hedonic shopping motivation has a significant positive effect on impulse buying for consumers.…”
Section: Hedonic Shopping Motivation To Impulsementioning
confidence: 93%
“…Hedonic shopping motivation and positive emotions are two factors that might drive customers to make spontaneous purchases or impulsive buying (Utami et al, 2021). According to Yu et al (2018), hedonic shopping buying is consumers shopping because they want to receive pleasure and shopping as something intriguing or consumers shopping because they feel joyful while they are shopping, either directly or online.…”
Section: Asia-pacificmentioning
confidence: 99%
See 2 more Smart Citations